Puding Rumput Laut: Inovasi Pangan untuk Meningkatkan Hemoglobin Ibu Hamil Anemia (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Anemia during pregnancy is a health problem that can increase the risk of complications for both mothers and fetuses. The utilization of local food as a complementary approach may support anemia prevention. This community service activity aimed to improve the knowledge, skills, and hemoglobin (Hb) levels of pregnant women with anemia through health education and a demonstration of seaweed pudding preparation. The activity was conducted in May 2026 in Banjararum Village, Singosari District, Malang Regency, involving 31 pregnant women with mild to moderate anemia. The method employed a participatory-educational approach through health counseling, demonstrations, hands-on practice, discussions, and evaluation using pretest–posttest assessments and Hb measurements before and 14 days after the intervention. The results showed an increase in the mean knowledge score from 58.7 ± 10.4 to 86.9 ± 7.2. The proportion of participants with good knowledge increased from 16.1% to 77.4%, while the proportion with poor knowledge decreased to 0%. The mean Hb level increased significantly from 9.82 ± 0.54 g/dL to 10.64 ± 0.60 g/dL (Δ = 0.82 ± 0.29 g/dL; p < 0.001). Furthermore, 90.3% of participants were able to prepare seaweed pudding independently. This activity demonstrates that demonstration-based education combined with the utilization of seaweed pudding has the potential to improve pregnant women's knowledge, skills, and Hb levels as part of promotive and preventive efforts to address anemia